STRATEGI EFEKTIF PEMBERANTASAN KORUPSI DI INDONESIA - Hendarto, Deni; Sulistyo, Eko (Jurnal Wahana Bina Pemerintahan, 2023)
The corruption that occurs in Indonesia is very worrying and has an extraordinary negative impact on almost all aspects of life. Therefore, there needs to be an effective strategy that can be used to overcome this problem. The aim of this research is to discuss various strategies that have been implemented and which can be the basis for a more effective eradication of corruption in Indonesia. This research uses a literature study method, which includes collecting, reading and documenting literature relevant to the research topic. The literature referred to is in the form of written works consisting of research results that have been published or not, and data sources are obtained from various sources, including books, journals and other references. Eradicating corruption requires public understanding of its negative impacts and developing a culture of integrity. The strategy to eradicate corruption must include changes in the behavior of officials, improved bureaucratic reform, increased supervision, firm law enforcement, and transparency in the management of state finances. Changes to laws and regulations that are more harmonious and comprehensive as well as better coordination between law enforcement agencies are key to eradicating corruption. The importance of strengthening an anti-corruption culture in society and effective education is also undeniable. Along with these efforts, Indonesia needs to ensure that the National Integrity System is well integrated, eliminating overlaps in corruption investigation authority between law enforcement agencies, and ensuring that these three institutions have equal roles and authority. With a holistic approach and comprehensive change, Indonesia can achieve a more effective eradication of corruption, contributing to improving societal welfare and national resilience in the future.